The Family Business Group Phenomenon Emergence and Complexities - Rautiainen, Marita; Rosa, Peter; Pihkala, Timo; Parada, Maria José; Cruz, Allan Discua (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
XXIII, 400 p. 24 illus.